Compensating, Mediating, and Moderating Effects of School Climate on Academic Achievement Gaps in Israel. Issue 7 (July 2015) - Berkowitz, Ruth; Glickman, Hagit; Benbenishty, Rami; Ben-Artzi, Elisheva; Raz, Tal; Lipshtat, Nurit; Astor, Ron Avi
Background: It is widely agreed among educational researchers and practitioners that schools with positive climates can effectively mitigate the influence of students' and schools' socioeconomic status (SES) on academic achievement. Nevertheless, the exact mechanisms by which this occurs are unclear. Objective: This study aimed to fill that gap, examining student perceptions of school climate, student academic achievement, and student and school SES in Israel to develop a reliable and comprehensive assessment of the role of school climate in the relationship between student and school SES and achievement. Specifically, the study tested whether school climate has an additive contribution to academics beyond students' and schools' SES (compensation model), whether the school's SES influences its social climate, which in turn influences academic achievement (mediation model); or whether the relationship between SES and academics changes across schools with different climates (moderation model). Research Design: Secondary analysis of a large-scale, nationally representative sample of fifth- and eighth-grade Hebrew-speaking students in public schools in Israel (N = 53, 946). Data Analysis: Hierarchical linear modeling (HLM) was used to examine models with variables both on the student and the school levels. Linear regressions were used to examine student level and school level only models. Results: School climate had an additive compensation contribution to academic achievements, both on the student and the school levels. School climate moderated the relationship between students' SES and academic achievements. However, findings did not support the hypothesis that school climate mediated the relationship between SES background and academic achievement, both at the student and school levels. Conclusions: School climate plays an important role in accounting for achievements, beyond students' and schools' SES. Results highlight the need to improve school climate, especially in schools serving communities of low SES, to enhance social mobility and equality of opportunity.